Simulation of Fuzzy Logic Controller for Improving the Efficiency of PV Systems Using MATLAB - arman, Muhammad Risky; Amalia, Sitti; Hidayat, Taufal; Bandri, Sepannur (Jurnal Ilmiah Telsinas, 2025)
Solar Power Plants (SPP) are one of the main solutions in the utilisation of renewable energy. However, their efficiency is often hampered by the variability of solar radiation and ambient temperature. To overcome this, Maximum Power Point Tracking (MPPT) technology is required so that solar panels always operate at the maximum power point (MPP). This study develops a Mamdani fuzzy logic-based MPPT system using MATLAB Simulink on a 10 WP PLTS prototype. The fuzzy algorithm is designed with two inputs, namely power and voltage, and one output in the form of a PWM signal to regulate energy conversion efficiency. Five test scenarios were conducted with different input combinations to compare the results of MATLAB simulations and manual calculations using the centroid weighted average method. The results show that the difference between simulation and manual calculations ranges from 1 to 11 PWM units (average <5%), with output classification remaining consistent in the Low, Medium, and High categories. This demonstrates that the Mamdani fuzzy manual method is valid and reliable as an adaptive control solution for PLTS systems. This implementation is expected to significantly improve energy conversion efficiency and support the achievement of national clean energy targets.